Relationship between innovation, regional institutions and firm performance: Micro-evidence from Africa - ÇOKGEZEN, MURAT (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The main aim of this paper is to examine empirically the extent to which firm-specific action, innovation, and an external factor, the quality of regional institution, affect firms' productivity. To this end, a firm-level dataset from 15 African countries was used and the three-step CDM approach was employed to estimate the relationship. The empirical results of the study highlight that firms that invest in R&D are more innovative and innovative firms are more productive, indicating the importance of innovation for firms' productivity. In addition, regional institutional quality has a significant positive effect on productivity, particularly for firms at low productivity distribution. Therefore, improving the quality of regional institutions, in addition to promoting R&D and innovation, is essential to enhance the productive capacity of firms in Africa. The present study contributes to the existing literature by providing new empirical evidence on the role of regional/local institutions on firm productivity for a region, Africa, which needs productivity enhancement the most. It is also recommended that further studies, similar to this one, should be carried out in order to better understand the topic in the context of African firms.
Keywords: innovation; productivity; regional institutions; CDM model; Africa